A Patient-Centered Documentation Skills Curriculum for Preclerkship Medical Students in an Open Notes Era - Kathleen Eng; Katherine Johnston; Ivo Cerda; Kushal Kadakia; Alison Mosier-Mills; Anita Vanka (Association of American Medical Colleges, 2024)
Introduction New legislation allows patients (with permitted exceptions) to read their clinical notes, leading to both benefits and ethical dilemmas. Medical students need a robust curriculum to learn documentation skills within this challenging context. We aimed to teach note-writing skills through a patient-centered lens with special consideration for the impact on patients and providers. We developed this session for first-year medical students within their foundational clinical skills course to place bias-free language at the forefront of how they learn to construct a medical note. Methods One hundred seventy-three first-year medical and dental students participated in this curriculum. They completed an asynchronous presession module first, followed by a 2-hour synchronous workshop including a didactic, student-led discussion and sample patient note exercise. Students were subsequently responsible throughout the year for constructing patient-centered notes, graded by faculty with a newly developed rubric and checklist of best practices. Results On postworkshop surveys, learners reported increased preparedness in their ability to document in a patient-centered manner (presession M = 2.2, midyear M = 3.9, p < .001), as rated on a 5-point Likert scale (1 = not prepared at all, 5 = very prepared), and also found this topic valuable to learn early in their training. Discussion This curriculum utilizes a multipart approach to prepare learners to employ clinical notes to communicate with patients and providers, with special attention to how patients and their care partners receive a note. Future directions include expanding the curriculum to higher levels of learning and validating the developed materials.